2014
DOI: 10.1111/1365-2745.12266
|View full text |Cite
|
Sign up to set email alerts
|

Desert shrub responses to experimental modification of precipitation seasonality and soil depth: relationship to the two‐layer hypothesis and ecohydrological niche

Abstract: Summary1. Ecohydrological niches are important for understanding plant community responses to climate shifts, particularly in dry lands. According to the two-layer hypothesis, selective use of deep-soil water increases growth or persistence of woody species during warm and dry summer periods and thereby contributes to their coexistence with shallow-rooted herbs in dry ecosystems. The resourcepool hypothesis further suggests that shallow-soil water benefits growth of all plants while deep-soil water primarily e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 48 publications
5
61
0
Order By: Relevance
“…Given the increasing frequency of climatic variability predicted by climate-change scenarios (Adler et al 2012, Cleland et al 2013, plant communities may be exposed to increasing instability at both local and regional scales (Bates et al 2006, Bai et al 2008, Heisler-White et al 2008, Bachman et al 2010, Cleland et al 2013, Germino and Reinhardt 2014. Although we cannot tease apart the role of climate from that of soil abiotic properties, our results indicate these factors combined may have contributed to different levels foliar damage, which in turn affected growth rate and survival.…”
Section: Discussionmentioning
confidence: 79%
“…Given the increasing frequency of climatic variability predicted by climate-change scenarios (Adler et al 2012, Cleland et al 2013, plant communities may be exposed to increasing instability at both local and regional scales (Bates et al 2006, Bai et al 2008, Heisler-White et al 2008, Bachman et al 2010, Cleland et al 2013, Germino and Reinhardt 2014. Although we cannot tease apart the role of climate from that of soil abiotic properties, our results indicate these factors combined may have contributed to different levels foliar damage, which in turn affected growth rate and survival.…”
Section: Discussionmentioning
confidence: 79%
“…For example, rougher soil surfaces and coarser soil textures can promote seed accumulation, germination, and the development of a tap root to access deeper soil moisture, with the latter being important for seedling survival (Chambers 2000, Germino and Reinhardt 2014, Brabec et al 2017. For example, rougher soil surfaces and coarser soil textures can promote seed accumulation, germination, and the development of a tap root to access deeper soil moisture, with the latter being important for seedling survival (Chambers 2000, Germino and Reinhardt 2014, Brabec et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…). Germino and Reinhardt () found that increases in winter precipitation increased big sagebrush canopy cover, due to higher soil water content in both upper and lower soil layers, but only on deep soils. Evidence from recent observations in western Wyoming indicate that extremely dry years may result in large big sagebrush die‐offs (Clause and Randall ) and smaller big sagebrush individuals may be particularly susceptible to drought‐related mortality due to small roots systems for water uptake (Campbell and Harris ).…”
Section: Discussionmentioning
confidence: 99%